Social Security and Income of Vulnerable Workers during Pandemic COVID-19 in Aceh - Cut Zakia Rizki; Putri Bintusy Syathi; Fitriyani Fitriyani (Proceedings of AICS - Social Sciences, 2021)
The pandemic has increased the number of vulnerable workers who are suffering from the pandemic. Vulnerable workers are workers who are sensitive to economic shocks. Since March 2020, restrictions on community activities have resulted in sluggish economic activity. There are some reductions in the fields of production, distribution, and consumption. The decrease in total production has an impact on the decrease in the number of production factors used, especially labor, both directly related workers and workers who are involved in the distribution or marketing process. These workers are very vulnerable to losing their jobs and affecting family acceptance. Therefore, this study investigates the compensation benefits received by vulnerable workers in the formal and informal sectors in Aceh Province affected by the COVID-19 pandemic. This study uses primary data obtained by interviews and questionnaires and also uses secondary data from related agencies. The method used in this research is descriptive qualitative which describes and analyzes a result by making a systematic, factual, and accurate description, picture, or painting about the facts, characteristics, and relationships between the phenomena investigated. The results of the field survey show that assistance programs aimed at reducing the impact of the pandemic are carried out at all levels of government, both central and local governments. These types of assistance are necessary to be implemented to reduce the impact of the pandemic. The aids are including Cash Social Assistance (BST) at the central government level and Social Security Program (JPS) from the Aceh Government sourced from the Aceh Revenue and Expenditure Budget (APBA).Keywords: Social Security, Social Assistance, Vulnerable Workers, Covid-19.